Buton Islam dan Islam Buton 1873 - 1938. Buton Islam and Islam Buton 1873 - 1938 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
History of Islam in Buton, 1873 until 1938, still maintains the typically characteristic. Syncretitation among principals of pre-Islam along with religious values of Islam has been actualized conditionally till the 20th. In 1873 until 1904 during the throne of Muhammad Salihi and Muhammad Umar, it still maintained the structure of the empire of Buton traditionally, particularly political culture and the system of empire as the predecessor.In 1906 till in the throne of sultan Muhammad Asyikin, Muhammad Husein, and Muhammad Aliy, the throne of empire was coopted by the political expansion of East Hindies which became the barrier for Islamic reform politically and lead Buton to culture association.During the throne of sultan Muhammad Syafiu, Muhammad Hamidi, and Muhammad Falihi between 1922 up to 1938, the directions of syncretitation development between the former belief and Islam was continued mainly "rohi polimba" belief (the moving spirit).